Problematika Pembelajaran Jarak Jauh Pada Masa Pandemi Covid-19 : (Studi Kasus di SMPIT Nurul Fajri – Cikarang Barat – Bekasi) - Afip Miftahul Basar (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: The learning process in schools during the Covid-19 pandemic had many problems to face. The Covid-19 pandemic that has hit the world, including Indonesia, requires taking a stand in preventing wider transmission, including the education sector. In this regard, the Ministry of Education and Culture has taken a firm stance through several circular letters relating to education policies in the emergency period of the spread of Covid-19. This paper examines the implementation of education policies during the Covid-19 pandemic related to distance learning policies. The distance learning process is a solution that is not yet optimal in its implementation. There are things that must be considered in this distance learning, among others, the quality of teacher resources must be improved, both in terms of content and methodology as well as in terms of the use of information technology. In addition, students are also less active in participating in this distance learning, both due to an unstable internet network and in terms of providing a limited internet quota. The purpose of writing this article is to study and understand the problems in learning activities during a pandemic, namely distance learning so that students can participate actively and interestingly. This study used a qualitative and observative approach. The results of this study prove that distance learning (PJJ) during the Covid-19 pandemic caused various responses and changes to the learning system that could affect the learning process and the level of development of students in responding to the material presented. Abstrak: Proses pembelajaran di sekolah pada masa pandemi Covid-19 mempunyai banyak permasalahan yang dihadapi. Pandemi Covid-19 yang melanda dunia termasuk Indonesia mengharuskan mengambil sikap dalam mencegah penularan yang lebih luas, termasuk sektor pendidikan. Berkaitan dengan hal tersebut Kementerian Pendidikan dan Kebudayaan mengambil sikap tegas melalui beberapa surat edaran berkaitan tentang kebijakan pendidikan dalam masa darurat penyebaran Covid-19. Tulisan ini mengkaji pelaksanaan kebijakan pendidikan dalam masa pandemi Covid-19 berkaitan dengan kebijakan pembelajaran jarak jauh. Proses pembelajaran jarak jauh merupakan solusi yang dalam pelaksanaannya belum optimal secara keseluruhan. Ada hal yang harus diperhatikan dalam pembelajaran jarak jauh ini antara lain sumber daya guru harus ditingkatkan kualitasnya, baik dari segi konten maupun metodologi juga dalam hal pemanfaatan teknologi informasi. Selain itu, peserta didik juga kurang aktif dalam mengikuti pembelajaran jarak jauh ini, baik itu disebabkan jaringan internet yang kurang stabil maupun dari segi penyediaan kuota internet yang terbatas. Tujuan penulisan artikel ini untuk mempelajari dan memahami permasalahan dalam kegiatan pemebelajaran di masa pandemi yakni pembelajaran jarak jauh agar peserta didik bisa mengikutinya dengan aktif dan menarik. Penelitian ini menggunakan pendekatan kualitatif dan observatif. Hasil kajian ini membuktikan bahwa pembelajaran jarak jauh (PJJ) di masa pandemi covid-19 ini menimbulkan berbagai tanggapan dan perubahan pada sistem belajar yang dapat mempengaruhi proses pemebelajaran serta tingkat perkembangan peserta didik dalam merespon materi yang disampaikan.